Leadership, psychoanalysis and society - Maccoby, Michael 1933-; Cortina, Mauricio (Routledge, 2022)
"Leadership Psychoanalysis, and Society describes leadership as a relationship between leaders and followers in a particular context and challenges theories of leadership now being taught. This book includes essays that view leadership from psychoanalytic, social psychological, sociological, evolutionary, developmental anthropological, and historical points of view to fully describe the complexity of leadership relationships and personalities. These essays analyze the different kinds of leadership needed in organizations; the development of Black Leadership that provides hope for people who have been oppressed; the difference between charismatic and inspirational leadership and the kind of training needed to develop leaders from diverse backgrounds who inspire followers and collaborate with them to further the common good. This book offers a guide to understanding the different types of leadership and will be of interest to business, government, health care, universities, and other organizations"--
Includes bibliographical references and index. - Print version record
Keywords: Leadership; Diversity in the workplace; Organizational learning; Organizational change; Organizational Innovation; Multiculturalisme en milieu de travail; Apprentissage organisationnel; Changement organisationnel; BUSINESS & ECONOMICS / Development / Business Development; BUSINESS & ECONOMICS / Consulting; PSYCHOLOGY / Movements / Psychoanalysis